PENGGUNAAN ZAT PENGATUR TUMBUH PADA PADI SULUTTAN UNSRAT 1 DAN SULUTTAN UNSRAT 2 - Polii-Mandang, Jeany Sh.; Doodoh, Beatrix; Tilaar, W. (Universitas Sam Ratulangi, 2020)
This research aims to discover the effects of Gibberellin, Kinetin, IAA, and Paclobutrazol growth regulators towards the growth and yield of suluttan unsrat 1 (SU1) and suluttan unsrat 2 (SU2) rice varieties. This research was done using split plots design with SU1 and SU2 varieties being the main plots and the subplots: Z0 (without plant growth regulator (PGR)); ZK (kinetin treatment); ZG (Giberellin treatment); ZI(IAA treatment); ZP (Paclobutrazol treatment).Â Each plot was replicated four times. Results show that there is no interaction between varieties and PGR treatment in temrs of growth variables, yield variables, and yield of SU1 and SU2. Gibberellin spray treatment in the beginning of reproductive stage increased plant height during harvest phase and length of rice panicle, but not increase grains per panicle. Individual treatments of IAA, Kinetin, Paclobutrazol growth regulators did not affect growth, yield, of SU1 and SU2. The timing, dosage, and frequency of PGR applications maybe was not yet optimal and did not increase the yield of SU1 and SU2 varieties.